Prevalence of anaemia and its associated factors among adolescent girls: a community based study - Gayakwad, Vasundara S.; Shankar, Gowri (International Journal Of Community Medicine And Public Health, 2019)
Background: Anemia is a major nutritional problem in adolescent girls in many developing countries. Anaemia prior to pregnancy is likely to affect fetal health and survival and therefore it is necessary to evaluate the nutritional needs in this vulnerable group. To know the prevalence of anaemia and its associated factors among adolescent girls residing in the urban field practice area of S. Nijalingappa Medical College, Bagalkot. Methods: A community based cross sectional study. A field practice areas of the urban health training centers, Department of Community Medicine, S. Nijalingappa Medical College in Bagalkot. 400 unmarried adolescent girls were participants. Systematic random sampling. Data was tabulated in Microsoft Excel 2010 and analyzed by using Open Epi software. Data was collected through predesigned, semi-structured questionnaire through house to house visits. Haemoglobin estimation was done by Sahli’s method and anaemia was classified based on WHO criteria. Results: The prevalence of anaemia was 63.3%. Factors associated with anemia were age, mother’s literacy, SES, type of family, environmental sanitation and tea consumption. Conclusions: Prevalence of anaemia is high and is a major public health problem in this area. Health education and periodical haemoglobin estimation followed by supplementation of iron would help in reduction and prevention of anaemia.